A conserved developmental program for sensory organ formation in Drosophila melanogaster. - Niwa, N.; Hiromi, Y.; Okabe, M. (Nature Genetics, 2004)
Different sensory organs, such the eye and ear, are widely thought to have separate origins, guided by distinct organ-specific factors that direct all aspects of their development. Previous studies of the D. melanogaster gene eyeless (ey) and its vertebrate homolog Pax6 suggested that this gene acts in such a manner and specifically drives eye development. But diverse sensory organs might instead arise by segment-specific modification of a developmental program that is involved more generally in sensory organ formation. In D. melanogaster, a common proneural gene called atonal (ato) functions in the initial process of development of a number of segment-specific organs, including the compound eye, the auditory organ and the stretch receptor, suggesting that these organs share an evolutionary origin. Here we show that D. melanogaster segment-specific sensory organs form through the integration of decapentaplegic (dpp), wingless (wg) and ecdysone signals into a single cis-regulatory element of ato. The induction of ectopic eyes by ey also depends on these signals for ato expression, and the ey mutant eye imaginal disc allows ato expression if cell death is blocked. These results imply that ey does not induce the entire eye morphogenetic program but rather modifies ato-dependent neuronal development. Our findings strongly suggest that various sensory organs evolved from an ato-dependent protosensory organ through segment specification by ey and Hox genes.